Existence of Solutions for a Singular Fractional q-Differential Equations under Riemann-Liouville Integral Boundary Condition - Samei, Mohammad Esmael; Ghaffari, Rezvan; Yao, Shao-Wen; Kaabar, Mohammed K. A.; Martinez, Francisco; İnç, Mustafa (Mdpi, 2021)
We investigate the existence of solutions for a system of m-singular sum fractional q-differential equations in this work under some integral boundary conditions in the sense of Caputo fractional q-derivatives. By means of a fixed point Arzela-Ascoli theorem, the existence of positive solutions is obtained. By providing examples involving graphs, tables, and algorithms, our fundamental result about the endpoint is illustrated with some given computational results. In general, symmetry and q-difference equations have a common correlation between each other. In Lie algebra, q-deformations can be constructed with the help of the symmetry concept.
Keywords: Caputo q-derivative; singular sum fractional q-differential; fixed point; equations; Riemann-Liouville q-integral